PNEUMOTHORAKS SPONTAN SEKUNDER REKUREN AKIBAT TUBERKULOSIS PARU RELAPS: LAPORAN KASUS - Reqgi First Trasia; Zenia Maulivia Fadila (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
Tuberculosis (TB) is an infectious disease that remains a major global public health problem and may lead to various complications, one of which is secondary spontaneous pneumothorax (SSP). Pneumothorax in TB occurs as a result of extensive damage to the lung parenchyma and pleura, potentially becoming a life-threatening condition that requires prompt management. This article aims to report and discuss a case of secondary spontaneous pneumothorax caused by pulmonary tuberculosis. A 29-year-old male presented to the emergency department with acute worsening dyspnea accompanied by right-sided chest pain, hemoptysis, decreased appetite, and a history of previous TB treatment. Physical examination revealed signs of respiratory distress with asymmetrical right chest wall movement, hyperresonance on percussion, and decreased breath sounds on the right side. Chest radiography and thoracic CT scan demonstrated active pulmonary tuberculosis with right-sided pneumothorax. Xpert MTB-RIF assay detected Mycobacterium tuberculosis with rifampicin sensitivity. The patient was diagnosed with secondary spontaneous pneumothorax due to recurrent pulmonary tuberculosis and received emergency management with tube thoracostomy followed by anti-tuberculosis therapy according to national guidelines. This case highlights the importance of early recognition of pneumothorax as a serious complication of tuberculosis, particularly in patients with a prior history of TB, and emphasizes the need for prompt diagnosis and comprehensive management to reduce morbidity and mortality.